Biosensor‐Enabled Multiplexed On‐Site Therapeutic Drug Monitoring of Antibiotics (Adv. Mater. 2/2022). Issue 2 (13th January 2022) - Ates, H. Ceren; Mohsenin, Hasti; Wenzel, Christin; Glatz, Regina T.; Wagner, Hanna J.; Bruch, Richard; Hoefflin, Nico; Spassov, Sashko; Streicher, Lea; Lozano‐Zahonero, Sara; Flamm, Bernd; Trittler, Rainer; et al.
Abstract : Personalized Antibiotherapy In article number 2104555, Can Dincer and co‐workers introduce an electrochemical multiplexed biosensor combined with a synthetic‐biology‐empowered assay, which enables a simple, yet accurate method to provide insights regarding the antibiotic levels even in exhaled breath condensate. The validated findings demonstrate the potential of the system to shift the paradigm of the "one size‐fits‐all" strategy for combating antibiotic resistance.